A qualitative study of the label of personality disorder from the perspectives of people with lived experience and occupational experience. Issue 1 (16th September 2021) - Lamph, Gary; Dorothy, Jake; Jeynes, Tamar; Coak, Alison; Jassat, Raeesa; Elliott, Alison; McKeown, Mick; Thornton, Tim
Abstract : Purpose: The label "Personality Disorder" continues to divide opinion. Challenges to the terminology of personality disorder led by people with lived experience and supported by critical practitioners and academics are tempered by acknowledgement of certain positive social consequences of obtaining a diagnosis. This study aims to engage service users and staff in a process of inquiry to better understand the complexities of views on the terminology of Personality Disorder. Design/methodology/approach: This study set out to qualitatively explore the views of a range of people with lived, occupational and dual lived experience/occupational expertise, relating to the diagnostic label of Personality Disorder, via participatory and critical group debate. The World Café approach is an innovative methodology for participatory inquiry into subjective views suited to exploring the contested subject matter. Findings: This study identified contrasting opinions towards the label of Personality Disorder and provides insight into the concerns described for both keeping and losing the label. Although many felt the words "personality" and "disorder" are not in themselves helpful, certain positive views were also revealed. Perspectives towards the label were influenced by the way in which diagnosis was explained and understood by patients and practitioners, alongside the extent to which service provision and evidence-based interventions were offered. Research limitations/implications: The findings have the potential to contribute to the ongoing critical debate regarding the value of the Personality Disorder construct in the provision of care and support. Specific emphasis upon the relational framing of care provision offers a means to ameliorate some of the negative impacts of terminology. Perspectives are influenced in the way the label is understood, hence, attention is required to enhance these processes in clinical practice. There is much more study required to overcome stigmatisation, prejudice, and lack of knowledge and understanding. Further research identifying means for challenging stigma and the factors contributing to positive clinical interactions are required. Originality/value: This study brings together a wide range of views and experiences of mental health professionals, individuals lived experiences and those who align to both lived and occupational expertise. A safe space was provided via the uniquely co-produced World Café research event to bring together discussion and debates from mixed perspectives makes this a novel study. The focus being on perspectives towards contested language, labelling and social impact adds to scholarship in this field.